Improving follow-up survey completion rates through pilot interventions in the All of Us Research Program: Results from a non-randomized intervention study. - Robert M Cronin; Xiaoke Feng; Ashley Able; Scott Sutherland; Ben Givens; Rebecca Johnston; Charlene Depry; Katrina W Le Blanc; Orlane Caro; Brandy Mapes; Josh Denny; Mick P Couper; et al. (PLoS ONE)
Objective Retention to complete follow-up surveys in extensive longitudinal epidemiological cohort studies is vital yet challenging. All of Us developed pilot interventions to improve response rates for follow-up surveys. Study design and setting The pilot interventions occurred from April 27, 2020, to August 3, 2020. The three arms were: (1) telephone appointment [staff members calling participants offering appointments to complete surveys over phone] (2) postal [mail reminder to complete surveys through U.S. Postal Service], and (3) combination of telephone appointment and postal. Controls received digital-only reminders [program-level digital recontact via email or through the participant portal]. Study sites chose their study arm and participants were not randomized. Results A total of 50 sites piloted interventions with 17,593 participants, while 47,832 participants comprised controls during the same period. Of all participants, 6,828 (10.4%) completed any follow-up surveys (1448: telephone; 522: postal; 486: combination; 4372: controls). Follow-up survey completions were 24% higher in the telephone appointment arm than in controls in bivariate analyses. When controlling for confounders, telephone appointment and combination arms increased rates of completion similarly compared to controls, while the postal arm had no significant effect (odds ratio [95% Confidence Interval], telephone appointment:2.01[1.81-2.23]; combination:1.91[1.66-2.20]; postal:0.92[0.79-1.07]). Although the effects of the telephone appointment and combination arms were similar, differential effects were observed across sub-populations. Conclusion Telephone appointments appeared to be the most successful intervention in our study. Lessons learned about retention interventions, and improvement in follow-up survey completion rates provide generalizable knowledge for similar cohort studies and demonstrate the potential value of precision reminders and engagement with sub-populations of a cohort.